DESAIN APLIKASI PERAMALAN PENYEWAAN LAPANGAN FUTSAL MENGGUNAKAN METODE DOUBLE EXPONENTIAL SMOOTHING - Saputri, Sasya Rahayu; Sinawati, Sinawati; lusi, lusiana (STMIK PPKIA Tarakanita Rahmawati, 2023)
The Futsal Field is a sports venue that is usually rented out by the hour. The problem that occurs is that there is no computerized system that is used to predict the number of rental hours on the futsal field for the next period, so that the owner can know whether in the next period it will increase or decrease. Based on the description above, the author wants to create an application that can predict the amount of rent on one of the futsal fields for the next period. The author will use Brown's Double Exponential Smoothing method to calculate the forecast, then to calculate the accuracy of the forecast calculation using the Mean Absolute Percentage Error method. This research produces an application that can predict the amount of field rent in the next 3 months. The results obtained are, in field 1 for January 2020 it was 136 hours, February 2020 was 136 hours, and March 2020 was 135 hours. Then in field 2, for January 2020 it is 74 hours, February 2020 is 74 hours, and March 2020 is 73 hours. The accuracy rates for fields 1 and 2 are 2.18% and 9.42%, which means very good.